A kind of anti-seepage and anti-cracking concrete and its production process
Through the process of pretreating aggregate and covering the capsule core, the problem of balance between concrete permeability and durability is solved, and the impermeability, carbonization resistance and crack resistance are improved, and a more dense concrete skeleton is built to enhance the The overall performance of concrete.
Patent Information
- Application Number
- CN202411371795.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing concrete is prone to reduced permeability and crack problems after long-term use, which affects its frost resistance, chemical corrosion resistance and carbonization resistance, and it is difficult to effectively solve the balance between permeability and durability.
Using a production process for anti-seepage and cracking, the production process of concrete is soaked in aqueous phosphoric acid solution and titanium tetrachloride solution to generate TiO2 doped aggregate, and the capsule core is coated with ethyl cellulose and silicon fume, combined with Polypropylene fiber and basalt fibers build a chamber skeleton to achieve self-healing and anti-carbonization effects.
The concrete's permeability, carbonization resistance and crack resistance are significantly improved. The cracks are filled through self-healing mechanisms, the aggregate's decomposition ability on CO2 is enhanced, the interface structure and filling effect are optimized, and the overall performance of concrete is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to an anti-seepage and anti-cracking concrete and a production process thereof. Background Art
[0002] There is a certain connection between concrete impermeability and durability, because permeability controls the rate at which external water, gas molecules and harmful ions penetrate the entire concrete structure, which is not only related to the waterproof and water-retaining effect of concrete, but also affects the concrete's frost resistance, chemical corrosion resistance and carbonation resistance. Therefore, improving concrete's impermeability plays an important role in the high performance of concrete. After long-term use, concrete will crack inside and on its surface, thus affecting the normal use function and durability of concrete. When the crack width exceeds a certain limit, it will affect the bearing capacity, stiffness and normal use function of concrete components. Summary of the invention
[0003] The purpose of the present invention is to provide an impermeability and crack resistance concrete and a production process thereof to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a production process of impermeable and crack-resistant concrete, comprising the following steps:
[0005] (1) Soak the aggregate in a 10% by mass phosphoric acid aqueous solution for 15 to 20 minutes, take out the aggregate, soak it in pure water for 10 minutes, take out the aggregate, and dry it at 100°C to constant weight to obtain the pretreated aggregate;
[0006] (2) The pretreated aggregate is soaked in a titanium tetrachloride aqueous solution with a mass fraction of 25-38%. After soaking for 5-8 hours, it is taken out and placed in a container, heated to 45-60°C, and the atomized droplets are transported to the surface of the pretreated aggregate by a carrier gas. The sodium hydroxide solution is atomized at an ultrasonic frequency of 20-60kHz. After treatment for 30-48 minutes, the temperature is raised to 80-100°C. Under the same conditions, deionized water is used as the atomizing liquid. After treatment for 20-30 minutes, an oxalic acid ethanol solution with a mass fraction of 10-20% is used as the atomizing liquid. After treatment for 40-50 minutes, it is taken out, dried at 100°C for 10 minutes, and then placed in a muffle furnace at 500°C for 1-2 hours to obtain TiO2-doped aggregate;
[0007] (3) The TiO2-doped aggregate is placed in a container, heated to 110-120°C, and the atomized droplets are transported by a carrier gas. A 25% sodium hydroxide aqueous solution is atomized at an ultrasonic frequency of 20-60kHz. After treating for 60-72 minutes, the aggregate is taken out, washed, dried at 80°C for 12 hours, and returned to the container. The aggregate is heated to 120-125°C, and an ammonium chloride-ethanol aqueous solution is used as the atomizing liquid. After treating for 1-2 hours, the aggregate is cooled to room temperature along with the container. A palladium nitrate solution is used as the atomizing liquid. After treating for 2-3 hours, the aggregate is taken out, dried at 100°C for 12 hours, and calcined at 450°C for 2 hours in an air atmosphere to obtain a modified aggregate.
[0008] (4) Gypsum and montmorillonite are mixed in a mass ratio of 1 to 3:1 and ground to a fineness of 600 to 800 mesh to obtain a capsule core; ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1 g:30 to 50 mL, stirred and heated in a constant temperature water bath at 50°C until fully dissolved to prepare a capsule wall liquid, which is evenly sprayed onto the surface of the capsule core while hot. After spraying, silica fume with a particle size of 1 to 10 μm is added. The capsule core is repeatedly turned over during the whole process, and the agglomerated capsule core is gently kneaded apart. After drying at 60 to 80°C to constant weight, a self-healing microcapsule is obtained;
[0009] (5) By weight, 15-25 parts of self-repairing microcapsules, 200-300 parts of silicate cement, 1100-1600 parts of modified aggregate, 120-180 parts of water, 10-20 parts of polypropylene fibers, 5-10 parts of polycarboxylic acid high-efficiency water reducing agent, and 2-10 parts of basalt fibers are mixed evenly to obtain impermeability and crack resistance concrete.
[0010] Furthermore, the aggregate in step (1) is obtained by mixing coarse aggregate with a particle size of 10-20 mm and fine aggregate with a particle size of 0.1-5 mm in a weight ratio of 40-60:70-90.
[0011] Furthermore, the sodium hydroxide solution in step (2) is a sodium hydroxide aqueous solution with a mass fraction of 10-30%.
[0012] Furthermore, the carrier gas in steps (2) and (3) is argon, and the gas flow rate is 50-300 mL / h.
[0013] Furthermore, the specific steps of washing in step (3) are: washing alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing solution is 7.
[0014] Furthermore, the concentration of the ammonium chloride-ethanol aqueous solution in step (3) is 0.1-0.12 g / mL, wherein the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1.
[0015] Furthermore, the palladium nitrate solution in step (3) is a palladium nitrate aqueous solution with a concentration of 0.05 mol / L.
[0016] Furthermore, in step (4), the ratio of the capsule core to the capsule wall liquid and the silica ash is 30 g:20~30 mL:30 g.
[0017] Furthermore, the viscosity of the ethyl cellulose in step (4) is 45-55 mPa·s, and the softening point is 100-135°C.
[0018] Furthermore, the polypropylene fiber in step (5) is a shaped polypropylene fiber with a length of 8-12 mm, a diameter of 6-8 μm, and a Y-shaped fiber cross-section; the basalt fiber has a length of 8-12 mm and a diameter of 3-5 μm.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention adopts a crushed mixture of gypsum and montmorillonite as the capsule core, ethyl cellulose as the capsule wall, and before solidification, the viscosity of ethyl cellulose is used for secondary coating, and the silica fume on the surface of the microcapsule reacts with cement, thereby driving the microcapsule to adhere to the cement surface, which can improve the interface structure in the concrete and block the capillaries in the slurry, thereby improving the impermeability and carbonization resistance. At the same time, when the stress generated by the cracking of the concrete can immediately cause the capsule wall to rupture, exposing the internal capsule core, and when the external water vapor or liquid flows in with the crack, the gypsum, montmorillonite and the surrounding concrete form crystals to fill the gaps, thereby achieving a self-repairing anti-cracking effect; and there is an obvious difference between the particle size of the modified aggregate and the microcapsule, which can improve the filling effect of the two, thereby constructing a more dense concrete skeleton together with polypropylene fiber and basalt fiber, thereby improving the anti-cracking performance of the concrete.
[0021] The present invention uses phosphoric acid to clean aggregates and improves aggregate porosity, which is beneficial to increasing the loading amount and growth of TiO2, thereby strengthening the decomposition of CO2 by aggregates and achieving the anti-carbonation effect of concrete; then the aggregates are immersed in a TiCl4 solution to fill the pores of the aggregates with titanium ions, then alkali spraying is performed to generate Ti(OH)4 solid inside the aggregates, acid spraying is performed to obtain aggregates doped with TiO2, CO2 is photocatalytically decomposed, the anti-carbonation effect of concrete is improved, and the pores of the aggregates are filled to prevent the formation of water flow channels inside the concrete, thereby optimizing the anti-seepage effect of the concrete; secondary alkali spraying is performed to convert TiO2 into a titanate structure, then ammonium salt is used to exchange hydrogen ions of the titanate to form ammonium titanate, palladium nitrate is used to perform cation exchange with the titanate to achieve Pd element surface doping, and finally, after calcination, the titanate is converted into TiO2, and Pd nanoparticles are generated on the surface, thereby effectively improving the photocatalytic ability of TiO2 and thereby improving the anti-carbonation effect of concrete. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1; (1) A coarse aggregate with a particle size of 10 mm and a fine aggregate with a particle size of 0.1 mm were mixed in a weight ratio of 40:70, and soaked in a 10% phosphoric acid aqueous solution. After soaking for 15 minutes, the aggregate was taken out, and then soaked in pure water for 10 minutes. The aggregate was taken out and dried at 100°C to constant weight to obtain a pretreated aggregate;
[0024] (2) The pretreated aggregate was soaked in a titanium tetrachloride aqueous solution with a mass fraction of 25%. After soaking for 5 hours, it was taken out and placed in a container, heated to 45°C, and argon was used as a carrier gas with a gas flow rate of 120 mL / h. The atomized droplets were transported to the surface of the pretreated aggregate by the carrier gas. A 10% sodium hydroxide aqueous solution was atomized at a 20 kHz ultrasonic frequency. After treatment for 30 minutes, the temperature was raised to 80°C. Under the same conditions, deionized water was used as the atomizing liquid. After treatment for 20 minutes, a 10% oxalic acid ethanol solution was used as the atomizing liquid. After treatment for 40 minutes, it was taken out, dried at 100°C for 10 minutes, and then placed in a muffle furnace for calcination at 500°C for 1 hour to obtain TiO2-doped aggregate;
[0025] (3) The TiO2-doped aggregate was placed in a container and heated to 110°C. Argon was used as a carrier gas with a gas flow rate of 120 mL / h. The atomized droplets were transported by the carrier gas. A 25% sodium hydroxide aqueous solution was atomized at an ultrasonic frequency of 20 kHz. After treatment for 60 min, the aggregate was taken out and washed alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing solution was 7. The aggregate was dried at 80°C for 12 h. The aggregate was returned to the container and heated to 120°C. An ammonium chloride-ethanol aqueous solution with a concentration of 0.1 g / mL was used as the atomizing liquid. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution was 1:1. After treatment for 1 h, the aggregate was cooled to room temperature with the container. A 0.05 mol / L palladium nitrate aqueous solution was used as the atomizing liquid. After treatment for 2 h, the aggregate was taken out and dried at 100°C for 12 h. The aggregate was calcined at 450°C for 2 h in an air atmosphere to obtain a modified aggregate.
[0026] (4) Gypsum and montmorillonite are mixed in a mass ratio of 1:1 and ground to a fineness of 600 mesh to obtain a capsule core; ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1g:30mL, stirred and heated in a constant temperature water bath at 50°C until fully dissolved to prepare a capsule wall liquid, which is evenly sprayed onto the surface of the capsule core while hot. After spraying, silica fume with a particle size of 1μm is added, and the capsule core is repeatedly turned over during the whole process, and the agglomerated capsule core is gently kneaded. The ratio of the capsule core to the capsule wall liquid and silica fume is 30g:20mL:30g. After drying at 60°C to constant weight, a self-healing microcapsule is obtained; the viscosity of the ethyl cellulose is 45~55mPa·s, and the softening point is 100~135°C;
[0027] (5) According to weight, 15 parts of self-repairing microcapsules, 200 parts of silicate cement, 1100 parts of modified aggregate, 120 parts of water, 10 parts of polypropylene fibers, 5 parts of polycarboxylic acid high-efficiency water-reducing agent, and 2 parts of basalt fibers are mixed evenly to obtain impermeability and crack resistance concrete; the polypropylene fibers are special-shaped polypropylene fibers with a length of 8 mm, a diameter of 6 μm, and a Y-shaped fiber cross-section; the basalt fibers are 8 mm in length and 3 μm in diameter.
[0028] Example 2; (1) A coarse aggregate with a particle size of 15 mm and a fine aggregate with a particle size of 2.2 mm were mixed in a weight ratio of 50:80, and soaked in a 10% by mass phosphoric acid aqueous solution. After soaking for 18 minutes, the aggregate was taken out, and then soaked in pure water for 10 minutes. The aggregate was taken out and dried at 100°C to constant weight to obtain a pretreated aggregate;
[0029] (2) The pretreated aggregate was soaked in a titanium tetrachloride aqueous solution with a mass fraction of 30%. After soaking for 6 hours, it was taken out and placed in a container, heated to 55°C, and argon was used as a carrier gas with a gas flow rate of 220 mL / h. The atomized droplets were transported to the surface of the pretreated aggregate by the carrier gas. A 20% sodium hydroxide aqueous solution was atomized at a 20 kHz ultrasonic frequency. After treatment for 40 minutes, the temperature was raised to 90°C. Under the same conditions, deionized water was used as the atomizing liquid. After treatment for 25 minutes, a 15% oxalic acid ethanol solution was used as the atomizing liquid. After treatment for 45 minutes, it was taken out, dried at 100°C for 10 minutes, and then placed in a muffle furnace for calcination at 500°C for 2 hours to obtain TiO2-doped aggregate;
[0030] (3) The TiO2-doped aggregate was placed in a container and heated to 115°C. Argon was used as a carrier gas with a gas flow rate of 220 mL / h. The atomized droplets were transported by the carrier gas. A 25% sodium hydroxide aqueous solution was atomized at an ultrasonic frequency of 20 kHz. After treatment for 66 min, the aggregate was taken out and washed alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing solution was 7. The aggregate was dried at 80°C for 12 h. The aggregate was returned to the container and heated to 122°C. An ammonium chloride-ethanol aqueous solution with a concentration of 0.11 g / mL was used as the atomizing liquid. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution was 1:1. After treatment for 2 h, the aggregate was cooled to room temperature with the container. A 0.05 mol / L palladium nitrate aqueous solution was used as the atomizing liquid. After treatment for 3 h, the aggregate was taken out and dried at 100°C for 12 h. The aggregate was calcined at 450°C for 2 h in an air atmosphere to obtain a modified aggregate.
[0031] (4) Gypsum and montmorillonite are mixed in a mass ratio of 2:1 and ground to a fineness of 600 mesh to obtain a capsule core; ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1g:40mL, stirred and heated in a constant temperature water bath at 50°C until fully dissolved to prepare a capsule wall liquid, which is evenly sprayed onto the surface of the capsule core while hot. After spraying, silica fume with a particle size of 5μm is added. The capsule core is repeatedly turned over during the whole process, and the agglomerated capsule core is gently kneaded. The ratio of the capsule core to the capsule wall liquid and silica fume is 30g:25mL:30g. After drying at 70°C to constant weight, a self-healing microcapsule is obtained; the viscosity of the ethyl cellulose is 45~55mPa·s, and the softening point is 100~135°C;
[0032] (5) According to weight, 20 parts of self-repairing microcapsules, 240 parts of silicate cement, 1300 parts of modified aggregate, 160 parts of water, 15 parts of polypropylene fibers, 6 parts of polycarboxylic acid high-efficiency water-reducing agent, and 6 parts of basalt fibers are mixed evenly to obtain impermeability and crack resistance concrete; the polypropylene fibers are special-shaped polypropylene fibers with a length of 12 mm, a diameter of 8 μm, and a Y-shaped fiber cross section; the basalt fibers are 8 mm in length and 5 μm in diameter.
[0033] Example 3; (1) A coarse aggregate with a particle size of 20 mm and a fine aggregate with a particle size of 5 mm were mixed in a weight ratio of 60:90, and soaked in a 10% by mass phosphoric acid aqueous solution. After soaking for 20 minutes, the aggregate was taken out, and then soaked in pure water for 10 minutes. The aggregate was taken out and dried at 100°C to constant weight to obtain a pretreated aggregate;
[0034] (2) The pretreated aggregate was soaked in a titanium tetrachloride aqueous solution with a mass fraction of 38%. After soaking for 8 hours, it was taken out and placed in a container, heated to 60°C, and argon was used as a carrier gas with a gas flow rate of 220 mL / h. The atomized droplets were transported to the surface of the pretreated aggregate by the carrier gas. A 30% sodium hydroxide aqueous solution was atomized at a 20 kHz ultrasonic frequency. After treatment for 48 minutes, the temperature was raised to 100°C. Under the same conditions, deionized water was used as the atomizing liquid. After treatment for 30 minutes, a 20% oxalic acid ethanol solution was used as the atomizing liquid. After treatment for 50 minutes, it was taken out, dried at 100°C for 10 minutes, and then placed in a muffle furnace for calcination at 500°C for 2 hours to obtain TiO2-doped aggregate;
[0035] (3) The TiO2-doped aggregate was placed in a container and heated to 120°C. Argon was used as a carrier gas with a gas flow rate of 220 mL / h. The atomized droplets were transported by the carrier gas. A 25% sodium hydroxide aqueous solution was atomized at an ultrasonic frequency of 20 kHz. After treatment for 72 minutes, the aggregate was taken out and washed alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing solution was 7. The aggregate was dried at 80°C for 12 hours. The aggregate was returned to the container and heated to 125°C. An ammonium chloride-ethanol aqueous solution with a concentration of 0.12 g / mL was used as the atomizing liquid. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution was 1:1. After treatment for 2 hours, the aggregate was cooled to room temperature with the container. A 0.05 mol / L palladium nitrate aqueous solution was used as the atomizing liquid. After treatment for 3 hours, the aggregate was taken out and dried at 100°C for 12 hours. The aggregate was calcined at 450°C in an air atmosphere for 2 hours to obtain the modified aggregate.
[0036] (4) Gypsum and montmorillonite are mixed in a mass ratio of 3:1 and ground to a fineness of 800 mesh to obtain a capsule core; ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1g:50mL, stirred and heated in a constant temperature water bath at 50°C until fully dissolved to prepare a capsule wall liquid, which is evenly sprayed onto the surface of the capsule core while hot. After spraying, silica fume with a particle size of 10μm is added. The capsule core is repeatedly turned over during the whole process, and the agglomerated capsule core is gently kneaded. The ratio of the capsule core to the capsule wall liquid and silica fume is 30g:30mL:30g. After drying at 80°C to constant weight, a self-healing microcapsule is obtained; the viscosity of the ethyl cellulose is 45~55mPa·s, and the softening point is 100~135°C;
[0037] (5) According to weight, 25 parts of self-repairing microcapsules, 300 parts of silicate cement, 1600 parts of modified aggregate, 180 parts of water, 20 parts of polypropylene fibers, 10 parts of polycarboxylic acid high-efficiency water reducing agent, and 10 parts of basalt fibers are mixed evenly to obtain impermeability and crack resistance concrete; the polypropylene fibers are special-shaped polypropylene fibers with a length of 12 mm, a diameter of 6 μm, and a Y-shaped fiber cross section; the basalt fibers are 12 mm in length and 5 μm in diameter.
[0038] Comparative Example 1: The only difference between Comparative Example 1 and Example 2 is that phosphoric acid is not used for pretreatment, and the remaining steps are the same as Example 2.
[0039] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: soak the pretreated aggregate in a titanium tetrachloride aqueous solution with a mass fraction of 30%, soak for 6 hours, take it out, place it in a container, use argon as a carrier gas, the gas flow rate is 220mL / h, and transport the atomized droplets to the surface of the pretreated aggregate by the carrier gas, heat it to 90°C, atomize a 15% oxalic acid ethanol solution at a 20kHz ultrasonic frequency, treat it for 45 minutes, take it out, dry it at 100°C for 10 minutes, and then place it in a muffle furnace at 500°C for calcination for 2 hours to obtain Ti-doped aggregate; step (3) is changed to: place the Ti-doped aggregate in a container, heat it to 115°C, use argon as a carrier gas, the gas flow rate is 220mL / h h, transport the atomized droplets through a carrier gas, atomize a 25% sodium hydroxide aqueous solution at a mass fraction at a 20kHz ultrasonic frequency, treat for 66 minutes, take out, wash alternately with 0.1mol / L hydrochloric acid solution and deionized water until the pH of the washing liquid is 7, dry at 80°C for 12 hours, put back into the container, heat to 122°C, use an ammonium chloride-ethanol aqueous solution with a concentration of 0.11g / mL as the atomizing liquid, and the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1. After treating for 2 hours, cool to room temperature with the container, use a 0.05mol / L palladium nitrate aqueous solution as the atomizing liquid, treat for 3 hours, take out, dry at 100°C for 12 hours, and calcine at 450°C for 2 hours in an air atmosphere to obtain a modified aggregate; the remaining steps are the same as in Example 2.
[0040] Comparative Example 3: The only difference between Comparative Example 3 and Example 2 is that the aggregate is not atomized using a 15% mass fraction oxalic acid ethanol solution, and the remaining steps are the same as Example 2.
[0041] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: the TiO2-doped aggregate is placed in a container, heated to 122°C, argon is used as a carrier gas, the gas flow rate is 220 mL / h, the atomized droplets are transported by the carrier gas, and an ammonium chloride-ethanol aqueous solution with a concentration of 0.11 g / mL is atomized at a 20 kHz ultrasonic frequency, the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1, after treating for 2 hours, the container is cooled to room temperature, 0.05 mol / L palladium nitrate aqueous solution is used as the atomizing liquid, after treating for 3 hours, the aggregate is taken out, dried at 100°C for 12 hours, and then calcined at 450°C in an air atmosphere for 2 hours to obtain a modified aggregate; the remaining steps are the same as Example 2.
[0042] Comparative Example 5; The only difference between Comparative Example 5 and Example 2 is that the aggregate is not atomized using an ammonium chloride-ethanol aqueous solution with a concentration of 0.11 g / mL, and the remaining steps are the same as Example 2.
[0043] Comparative Example 6: The only difference between Comparative Example 6 and Example 2 is that the aggregate is not atomized using a 0.05 mol / L aqueous palladium nitrate solution, and the remaining steps are the same as Example 2.
[0044] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (3) is different. Step (3) is changed to: the TiO2-doped aggregate is placed in a container, heated to 115°C, argon is used as a carrier gas, the gas flow rate is 220 mL / h, the atomized droplets are transported by the carrier gas, a 25% mass fraction of sodium hydroxide aqueous solution is atomized at an ultrasonic frequency of 20 kHz, after treatment for 66 min, taken out, washed alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing liquid is 7, dried at 80°C for 12 h, returned to the container, heated to 122°C, and an ammonium chloride-ethanol aqueous solution with a concentration of 0.11 g / mL is used as the atomizing liquid, the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:1, after treatment for 2 h, the container is cooled to room temperature, 0.05 mol / L palladium nitrate aqueous solution is used as the atomizing liquid, after treatment for 3 h, taken out, and dried at 100°C for 12 h to obtain the modified aggregate; the remaining steps are the same as Example 2.
[0045] Comparative Example 8: The only difference between Comparative Example 8 and Example 2 is that the surface of the self-repairing microcapsule is not coated with silica fume, and the remaining steps are the same as Example 2.
[0046] Comparative Example 9: The difference between Comparative Example 9 and Example 2 is that step (4) is omitted, and step (5) is changed to: gypsum and montmorillonite are mixed in a mass ratio of 2:1 and ground to a fineness of 600 mesh to obtain a filler, and 20 parts of filler, 10 parts of silica fume, 240 parts of silicate cement, 1300 parts of modified aggregate, 160 parts of water, 15 parts of polypropylene fiber, 6 parts of polycarboxylic acid high-efficiency water reducing agent, and 6 parts of basalt fiber are mixed uniformly by weight to obtain impermeability and crack resistance concrete; the polypropylene fiber is a special-shaped polypropylene fiber with a length of 12 mm, a diameter of 8 μm, and a Y-shaped fiber cross-section; the basalt fiber has a length of 8 mm and a diameter of 5 μm; the remaining steps are the same as Example 2.
[0047] Effect example
[0048] With reference to GB / T50082 and GB / T50081, the carbonization height, penetration height and compressive strength tests were carried out on the impermeability and crack resistant concrete of Examples 1 to 3 of the present invention and Comparative Examples 1 to 9; with reference to CN202211183736.8, the crack resistance and self-repairing performance after curing of the impermeability and crack resistant concrete of Examples 1 to 3 of the present invention and Comparative Examples 1 to 9 were tested, and the crack resistance grade was used.
[0049] Table 1
[0050]
[0051] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention adopts silica fume coated microcapsules as self-repairing fillers for concrete. When the stress generated by the cracking of concrete can cause the capsule wall to rupture in the first time, exposing the internal capsule core. When the external water vapor or liquid flows in with the cracks, the capsule core and the surrounding concrete form crystals to fill the gaps, thereby achieving a self-repairing anti-cracking effect. The microcapsules adhere to the cement surface, which can improve the interface structure in the concrete and block the capillaries in the slurry, thereby improving the impermeability. The present invention adopts Pd-TiO2 modified aggregate to achieve photocatalytic decomposition of CO2 and improve the anti-carbonization effect of concrete. At the same time, the presence of Pd-TiO2 fills the gaps in the aggregate and improves the strength of the aggregate, thereby improving the impermeability, anti-carbonization and mechanical properties of the concrete. The present invention effectively regulates the obvious difference between the particle size of the modified aggregate and the microcapsule, which can improve the filling effect of the two, thereby constructing a more dense concrete skeleton together with polypropylene fiber and basalt fiber, thereby improving the anti-cracking performance of the concrete.
[0052] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A production process for impermeable and crack-resistant concrete, characterized in that: The following steps are involved: (1) Soak the aggregate in a 10% by mass phosphoric acid aqueous solution for 15 to 20 minutes, take out the aggregate, soak it in pure water for 10 minutes, take out the aggregate, and dry it at 100°C to constant weight to obtain the pretreated aggregate; (2) The pretreated aggregate is soaked in a titanium tetrachloride aqueous solution with a mass fraction of 25-38%. After soaking for 5-8 hours, it is taken out and placed in a container, heated to 45-60°C, and the atomized droplets are transported to the surface of the pretreated aggregate by a carrier gas. The sodium hydroxide solution is atomized at an ultrasonic frequency of 20-60kHz. After treatment for 30-48 minutes, the temperature is raised to 80-100°C. Under the same conditions, deionized water is used as the atomizing liquid. After treatment for 20-30 minutes, an oxalic acid ethanol solution with a mass fraction of 10-20% is used as the atomizing liquid. After treatment for 40-50 minutes, it is taken out, dried at 100°C for 10 minutes, and then placed in a muffle furnace at 500°C for 1-2 hours to obtain TiO2-doped aggregate; (3) The TiO2-doped aggregate is placed in a container, heated to 110-120°C, and the atomized droplets are transported by a carrier gas. A 25% sodium hydroxide aqueous solution is atomized at an ultrasonic frequency of 20-60kHz. After treating for 60-72 minutes, the aggregate is taken out, washed, dried at 80°C for 12 hours, and returned to the container. The aggregate is heated to 120-125°C, and an ammonium chloride-ethanol aqueous solution is used as the atomizing liquid. After treating for 1-2 hours, the aggregate is cooled to room temperature along with the container. A palladium nitrate solution is used as the atomizing liquid. After treating for 2-3 hours, the aggregate is taken out, dried at 100°C for 12 hours, and calcined at 450°C for 2 hours in an air atmosphere to obtain a modified aggregate. (4) Gypsum and montmorillonite are mixed in a mass ratio of 1 to 3:1 and ground to a fineness of 600 to 800 mesh to obtain a capsule core; ethyl cellulose and anhydrous ethanol are mixed in a ratio of 1 g:30 to 50 mL, stirred and heated in a constant temperature water bath at 50°C until fully dissolved to prepare a capsule wall liquid, which is evenly sprayed onto the surface of the capsule core while hot. After spraying, silica fume with a particle size of 1 to 10 μm is added. The capsule core is repeatedly turned over during the whole process, and the agglomerated capsule core is gently kneaded apart. After drying at 60 to 80°C to constant weight, a self-healing microcapsule is obtained; (5) By weight, 15-25 parts of self-repairing microcapsules, 200-300 parts of silicate cement, 1100-1600 parts of modified aggregate, 120-180 parts of water, 10-20 parts of polypropylene fibers, 5-10 parts of polycarboxylic acid high-efficiency water reducing agent, and 2-10 parts of basalt fibers are mixed evenly to obtain impermeability and crack resistance concrete.
2. The production process of a permeability-resistant and crack-resistant concrete according to claim 1, characterized in that: The aggregate in step (1) is obtained by mixing coarse aggregate with a particle size of 10-20 mm and fine aggregate with a particle size of 0.1-5 mm in a weight ratio of 40-60:70-90.
3. The production process of a permeability-resistant and crack-resistant concrete according to claim 1, characterized in that: The sodium hydroxide solution in step (2) is a sodium hydroxide aqueous solution with a mass fraction of 10-30%.
4. The production process of a permeability-resistant and crack-resistant concrete according to claim 1, characterized in that: The carrier gas in steps (2) and (3) is argon, and the gas flow rate is 50-300 mL / h.
5. The production process of a permeability and crack resistance concrete according to claim 1, characterized in that: The specific steps of washing in step (3) are: washing alternately with 0.1 mol / L hydrochloric acid solution and deionized water until the pH of the washing solution is 7.
6. The production process of a permeability-resistant and crack-resistant concrete according to claim 1, characterized in that: The concentration of the ammonium chloride-ethanol aqueous solution in step (3) is 0.1-0.12 g / mL, wherein the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:
1.
7. The production process of a permeability and crack resistance concrete according to claim 1, characterized in that: The palladium nitrate solution in step (3) is a palladium nitrate aqueous solution with a concentration of 0.05 mol / L.
8. The production process of the impermeability and crack resistance concrete according to claim 1, characterized in that: In step (4), the ratio of the capsule core to the capsule wall liquid and the silica ash is 30 g:20-30 mL:30 g.
9. The production process of a permeability and crack resistance concrete according to claim 1, characterized in that: The viscosity of the ethyl cellulose in step (4) is 45-55 mPa·s, and the softening point is 100-135°C.
10. The production process of the impermeability and crack resistance concrete according to claim 1, characterized in that: The polypropylene fiber in step (5) is a special-shaped polypropylene fiber with a length of 8-12 mm, a diameter of 6-8 μm, and a Y-shaped fiber cross-section; the basalt fiber has a length of 8-12 mm and a diameter of 3-5 μm.
